Ventilation and posture effects on inhalation exposures to volatile cleaning ingredients in a simulated domestic worker cleaning environment. (29th July 2020) - Benjamin, Michael L.; Arnold, Susan; Rao, Marepalli; Davis, Kermit; Maier, Andrew; Virkutyte, Jurate
Abstract: Associations between cleaning chemical exposures and asthma have previously been identified in professional cleaners and healthcare workers. Domestic workers, including housecleaners and caregivers, may receive similar exposures but in residential environments with lower ventilation rates. Study objectives were to compare exposures to occupational exposure limits (OELs), to determine relative contributions from individual cleaning tasks to overall exposure, and to evaluate the effects of ventilation and posture on exposure. Airborne chemical concentrations of sprayed cleaning chemicals (acetic acid or ammonia) were measured during typical cleaning tasks in a simulated residential work environment. Whole‐house cleaning exposures (18 cleaning tasks) were measured using integrated personal sampling methods. Individual task exposures were measured with a sampling line attached to subjects' breathing zones, with readings recorded by a ppbRAE monitor, equipped with a photoionization detector calibrated for ammonia and acetic acid measurements. Integrated sampling results indicated no exposures above OELs occurred, but 95th percentile air concentrations would require risk management decisions. Exposure reductions were observed with increased source distance, with lower exposures from mopping floors compared to kneeling. Exposure reductions were also observed for most but not all tasks when ventilation was used, with implications that alternative exposure reduction methods may be needed.